Effectiveness of Massage on Hemodialysis Complications: A Systematic Review and Meta-Analysis - Rusyda Anshari; Masfuri Masfuri; Anggri Noorana Zahra; Sri Yona (Glosains: Jurnal Sains Global Indonesia, 2026)
Background: Patients undergoing hemodialysis frequently experience complications such as fatigue, restless legs syndrome, pruritus, and sleep disturbances that impair their quality of life. Although individual trials have suggested that massage therapy may alleviate these complications, no previous systematic review has synthesized its overall effectiveness across multiple hemodialysis-related outcomes. Objective: To evaluate the effectiveness of massage therapy in managing hemodialysis-related complications and to identify the key characteristics of massage interventions. Methods: This systematic review and meta-analysis followed the PRISMA 2020 guidelines. Articles published between 2019 and 2025 were identified through searches of six databases: ScienceDirect, Scopus, EBSCOhost, PubMed, Wiley, and ProQuest. The methodological quality of the included studies was assessed using the Cochrane Risk of Bias tool, and data were analyzed using Comprehensive Meta-Analysis (CMA) software. Results: Eighteen randomized controlled trials involving a total of 1,383 patients undergoing hemodialysis were included in the meta-analysis. The pooled effect sizes indicated that massage interventions were effective in reducing fatigue (SMD = −0.88, 95% CI: −1.27 to −0.49), restless legs syndrome (SMD = −1.62, 95% CI: −2.31 to −0.93), and pruritus (SMD = −1.34, 95% CI: −2.65 to −0.03), while significantly improving sleep quality (SMD = 1.05, 95% CI: 0.63 to 1.47) and quality of life (SMD = 0.56, 95% CI: 0.31 to 0.81). Variations in massage techniques and intervention duration demonstrated differential effects on hemodialysis-related complications. Conclusion: Massage therapy, as a nonpharmacological intervention, was associated with improvements in several hemodialysis-related complications. However, the substantial between-study heterogeneity (I² = 42%–93%) warrants cautious interpretation of the findings. Massage therapy appears to be a low-cost, generally safe, noninvasive adjunctive intervention with minimal reported adverse effects for patients undergoing hemodialysis.